Radiographic Ischial Enthesopathy in Patients with Psoriatic Arthritis - Bitik, Berivan; Dalgic, Gunay Sahin; Kanbur, Aysenur Yalcintas; Ok, Mehtap Akcil; Yucel, Ahmet Eftal (Aktuelle Rheumatologie, 2022)
Background To investigate the prevalence of radiographic ischial entheseal lesions in patients with psoriatic arthritis (PsA) compared to patients with rheumatoid arthritis (RA).Patients and Methods Thirty-eight patients with PsA and 46 patients with RA were included. Anteroposterior radiographs of the pelvis and lateral foot were evaluated for entheseal lesions. The following entheseal sites were reviewed: os ischium, bilateral Achilles tendon and inferior calcaneus. Abnormalities such as cortical erosions and enthesophytes (irregular bony proliferation) were recorded.Results The frequency of enthesopathic changes in the ischial region was found to be statistically significantly higher in PsA patients compared with RA patients (50 and 28.3%, respectively, p=0.04). Enthesopathic changes of the calcaneus and Achilles tendon also occurred more frequently in PsA patients than in RA patients.Conclusion Radiographic entheseal lesions in the ischial region are more prevalent in PsA patients compared with RA patients with symptoms in that region. Furthermore, such enthesopathic changes in the ischium are observed as frequently as changes in the Achilles tendon. These findings regarding structural entheseal lesions in the pelvic region contribute to the knowledge of entheseal involvement in PsA.
Keywords: ischium; psoriatic arthritis; rheumatoid arthritis; enthesitis